A collaborative e-workspace for digital library of Malay manuscripts - Zulkifli, Zahidah (International Journal of Information and Education Technology (IJIET), 2014)
Philology studies are often associated with traditional methods of teaching and learning. This study shows the best tools that can be implemented in order to make a collaborative work among Malay manuscripts community. The Soft System Methodology (SSM) is used to guide the investigation. The manuscript community comprises lecturers, students and researchers in the field of philology. Data were gathered from interviews, focus group discussions and observations. Academy of Malay Studies, University of Malaya is the case study setting, focusing on lecturers who teach and students who enrol in a philology course as well as doctoral students researching on manuscript studies. The findings highlight the features and modules that are available in the Malay manuscripts collaborative e-workspace in order to improve teaching, learning and researching as well as utilizing digitized manuscript surrogates held in a digital library of Malay manuscripts.